Analysis of the Effect of Powtoon Application Interactive Learning Media on Mathematics Learning Ability of Elementary School Students - Soraya Rizki Ananda; Zulfadewina Zulfadewina (Universitas Pendidikan Mandalika, 2023)
This study aims to see the positive and significant effect of interactive learning media on the application of powtoon in developing the learning abilities of fourth-grade students at SDN Pekayon 12 in learning mathematics. This study used the Tru-Experiment research method, using a post-test-only design. The samples came from Class IV A and B, with 27 students in Class A and 24 in Class B. Research instruments are measuring tools to do something and research tools to collect data as processed materials. One instrument makes it easy to measure, collect, compare and process. Whether or not a research instrument is determined by its validity and reliability. Instrument validity is the accuracy with which you measure what you want to measure, and reliability reflects variable data correctly and does not deviate from the actual situation. The instrument is valid if it can provide reliable data consistent with the actual situation. Instruments are said to be reliable when they can reveal reliable data. The results of this study indicated an effect of interactive learning media on the application of powtoon on students' learning abilities in learning mathematics in class IV SDN Pekayon 12. This was evidenced by the data of the Validity Test, Reliability Test, Normality Test (Lillifors Test), Homogeneity Test (Fisher's Test) and T-Test.